Analisis Motivasi Berprestasi Mahasiswa Dalam Sistem Pembelajaran Berbasis blended learning Era Industri 4.0 - Ardian Cahyadi; Suarli Suarli; Candra Kurniawan (Universitas Lampung, 2021)
The purpose of this study was to determine student profiles and the percentage of student achievement motivation in a blended learning-based learning system in the industrial era 4.0. The sampling technique used was stratified random sampling with cluster sampling. Total sample: 120 participants (30 x 4 classes = 120). From the data analysis, it can be seen that achievement motivation data results include, 33% of students have very high motivation, 38% high motivation, 17% moderate motivation, 8% less motivation, and 4% very low motivation. Overall student motivation in digital-based learning systems is very good, it can be seen from the results of data analysis that has been carried out, learning systems that can provoke interest in learning are very influential on increasing motivation, and conversely high motivation will be able to form a personality that is ready in various situations. no exception to the adaptation of the learning system that continues to grow.Keywords: Achievement Motivation, Learning System, Blended LearningDOI: http://dx.doi.org/10.23960/jiip.v3i1.23269